Neuropilin‐2 and its ligand VEGF‐C predict treatment response after transurethral resection and radiochemotherapy in bladder cancer patients. Issue 2 (12th June 2014) - Keck, B.; Wach, S.; Taubert, H.; Zeiler, S.; Ott, O.J.; Kunath, F.; Hartmann, A.; Bertz, S.; Weiss, C.; Hönscheid, P.; Schellenburg, S.; Rödel, C.; et al.
<x xml:space="preserve">Abstract</x> The standard treatment for invasive bladder cancer is radical cystectomy. In selected patients, bladder‐sparing therapy can be performed by transurethral resection (TURBT) and radio‐chemotherapy (RCT) or radiotherapy (RT). Our published in vitro data suggest that the Neuropilin‐2 (NRP2)/VEGF‐C axis plays a role in therapy resistance. Therefore, we studied the prognostic impact of NRP2 and VEGF‐C in 247 bladder cancer patients (cN0M0) treated with TURBT and RCT (n = 198) or RT (n = 49) and a follow‐up time up to 15 years. A tissue microarray was analyzed by immunohistochemistry. NRP2 expression emerged as a prognostic factor in overall survival (OS; HR: 3.42; 95% CI: 1.48 – 7.86; p = 0.004) and was associated with a 3.85‐fold increased risk of an early cancer specific death (95% CI: 0.91 – 16.24; p = 0.066) in multivariate analyses. Cancer specific survival (CSS) dropped from 166 months to 85 months when NRP2 was highly expressed (p = 0.037). Patients with high VEGF‐C expression have a 2.29‐fold increased risk of shorter CSS (95% CI: 1.03–5.35; p = 0.043) in univariate analysis. CSS dropped from 170 months to 88 months in the case of high VEGF‐C expression (p = 0.041). Additionally, NRP2 and VEGF‐C coexpression is a prognostic marker for OS in multivariate models (HR: 7.54; 95% CI: 1.57–36.23; p = 0.012). Stratification for muscle invasiveness (T1 vs. T2‐T4) confirmed the prognostic role of NRP2 and NRP2/VEGF‐C co‐expression in patients with T2‐T4 but also with high risk T1 disease. In conclusion, immunohistochemistry for NRP2 and VEGF‐C has been determined to predict therapy outcome in bladder cancer patients prior to TURBT and RCT.